2013
DOI: 10.1007/s00248-013-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Reveals Contrasting Soil Bacterial Diversity and Community Structure of Two Main Winter Wheat Cropping Systems in China

Abstract: Microbes are key components of the soil environment, playing an important role in maintaining soil health, sustainability, and productivity. The composition and structure of soil bacterial communities were examined in winter wheat-rice (WR) and winter wheat-maize (WM) cropping systems derived from five locations in the Low-Middle Yangtze River plain and the Huang-Huai-Hai plain by pyrosequencing of the 16S ribosomal RNA gene amplicons. A total of 102,367 high quality sequences were used for multivariate statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 52 publications
16
100
0
Order By: Relevance
“…In the present study, we found that the proportions of abundant taxa were highly negatively correlated with soil pH, EC, and SOC. Our results were consistent with some other studies that have demonstrated that soil pH was a very strong factor in structuring microbial communities [31,81]. In contrast, the proportions of abundant taxa were positively correlated with soil available P and K ( Table 2).…”
Section: The Relationships Between Microorganism Taxa and Soil Featursupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, we found that the proportions of abundant taxa were highly negatively correlated with soil pH, EC, and SOC. Our results were consistent with some other studies that have demonstrated that soil pH was a very strong factor in structuring microbial communities [31,81]. In contrast, the proportions of abundant taxa were positively correlated with soil available P and K ( Table 2).…”
Section: The Relationships Between Microorganism Taxa and Soil Featursupporting
confidence: 82%
“…The results were also confirmed by the redundancy analysis (RDA) of the abundant taxa and the environmental variables for individual samples during the three years ( Figure 6). Our results are consistent with reports that the physicochemical soil microenvironment has a very strong impact on soil microbial community and structure [31,82,83]. Until now, this interaction between environmental variables and the fungal community has proved to be beneficial to cucumber plants.…”
Section: The Relationships Between Microorganism Taxa and Soil Featursupporting
confidence: 82%
See 1 more Smart Citation
“…Firmicutes have been described as fast-growing copiotrophs that thrive in environments with high carbon availability (Rodrigues et al 2013). Among the classes of Firmicutes, the relative abundance of Bacilli, which are primarily obligate aerobes (Zhao et al 2014), was significantly higher in the chisel plow and zero tillage soils than it was in the plow tillage. The genus Bacillus, which belongs to the class Bacilli and possesses numerous growth-promoting characteristics and is adapted to local conditions (Abiala et al 2015), was the most represented among the Firmicutes in chisel plow and zero tillage (85 % each).…”
Section: Effects Of Different Tillage Protocols On Soil Bacterial Taxmentioning
confidence: 90%
“…Measurements of pH, soil organic carbon, total nitrogen, and soil texture were performed as described by Zhao et al (2014). The soil concentrations of inorganic nitrogen (nitrate and ammonia) and dissolved organic carbon and nitrogen were determined using the procedure described by Berthrong et al (2013).…”
Section: Soil Sampling and Physicochemical Analysismentioning
confidence: 99%